Assessment of anaerobic threshold and performance of swimmers in crawl sprints of 400m - Guglielmo, L. G.; Denadai, B. S. (Medicine & Science in Sports & Exercise, 1999)
The relationships between arm and pool tests that yield anaerobic threshold estimates and 400-m crawl stroke performance were determined. Male swimmers (N = 9) performed the following activities: a 400-m time trial (TT); 3 x 400 m at intensities of 80%, 85%, 90% of best velocity to determine anaerobic threshold (IP), and a continuous (CL) and intermittent tests (IL) on an arm ergometer to determine anaerobic thresholds. Estimates of anaerobic threshold were significantly related between IP and CL (r = .72), but not significantly related between IL and IP. Swimming time was significantly related to anaerobic threshold estimates in CL and IP. IP was the best test for estimating 400-m velocity while CL also offered a reasonable estimate. Implication: The estimate of anaerobic threshold derived from performing a set of three increasing intensity submaximal 400-m swims was the best predictor of 400-m swimming time. However, the time taken to conduct that series of swims is much greater than that required by the criterion swim itself. Thus, the best test for evaluating 400-m performance is simply to swim the distance as fast as possible.